Regime-switching model of electricity prices for the Philippine energy market - Aspera,Donna Corpuz; David,Fredegusto Guido (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2014)
To date,here has been no adequate model of energy prices in the Philippines. In this paper, a regime-switching approach is used to model the dynamics of electricity spot prices of the Philippine Wholesale Electricity Spot Market. Three regimes are considered to characterize a base regime, an upward spik regime, and a downward spike regime. The parameters of the model are estimated and used to numerically forecast point and interval estimates for a three-month out-of-sample data. The forecasts are then compared with actual realized electricity prices.
Thesis (M.S. Applied Mathematics)--University of the Philippines Diliman
Keywords: Switching circuits; Electricity